2021
DOI: 10.12968/ijpn.2021.27.9.464
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Spirituality in Palliative Care Scale for nursing students in the context of Thai culture

Abstract: Background: Nursing students form part of the healthcare team who care for patients who are living with a terminal illness and facing physical and spiritual suffering. However, there is a lack of suitable indicators to measure a nurse's spirituality when they are providing palliative care. Aim: To develop a way of measuring the spirituality of nurses who provide palliative care. Method: The participants consisted of 312 third-and fourth-year nursing students of two nursing colleges from southern and central Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…reported that all participants in the study doubted about their existing knowledge. Sukcharoen et al (2020) investigated the effect of transformative learning on spirituality in a study conducted with the participation of nursing students. In the study, it was determined that the participants doubted about their beliefs and values.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…reported that all participants in the study doubted about their existing knowledge. Sukcharoen et al (2020) investigated the effect of transformative learning on spirituality in a study conducted with the participation of nursing students. In the study, it was determined that the participants doubted about their beliefs and values.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the past, Thai palliative care concept didn’t apply with the terminal ill patients. Only interdisciplinary team took care before their death [ 4 , 5 ]. Their families still hope patients recover from complex disease that can’t be cured to reduce patients’ pain and suffering hopefully they would be discharged from the ICU to their house [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only interdisciplinary team took care before their death [ 4 , 5 ]. Their families still hope patients recover from complex disease that can’t be cured to reduce patients’ pain and suffering hopefully they would be discharged from the ICU to their house [ 5 ]. Therefore, a need for specific care has arisen, especially ICU palliative care to ensure human dignity for patients and their families at end-of-life stage and after the patients’ deaths [ 2 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations